PERAN REMAJA DALAM MENGURANGI SAMPAH PLASTIK DI LINGKUNGAN SEKOLAH - Wasiman; Alice Erni Husein; Realize Realize; Mauli Siagian; Asron Saputra (ASOSIASI IDEBAHASA KEPRI, 2026)
Community Service is an obligation that must be carried out by a lecturer as a form of responsibility for the knowledge they have so that they can share knowledge with the community. The implementation of community service with the title The Role of Teenagers in Reducing Plastic Waste in Schools is an invitation to live a clean culture from an early age and cleanliness is a shared responsibility that must always be instilled from an early age. Instilling cleanliness at an early age will shape the culture and character of adolescents in life at school or in society and is a reflection of a form of concern for a clean environment so as to provide awareness in a clean environment. The role of adolescents in creating a clean environment, namely: 1) Throwing trash in the place provided by the school, 2) inviting other school friends to maintain the cleanliness of the school, 3) Providing education about the importance of clean living in the school environment, 4) the principles of Reduce (Reducing waste) Reuse (Reusing) and Recycle (Recycling) and explaining to students about separating waste according to its type. A clean school culture is also the responsibility of all parties in the school and this reflects a shared awareness that must always be considered and always educated to all students so that a clean environment becomes an absolute must for all parties.